Patterns of Supervision and Management of School Principles for Increasing Teacher Performance SDIT Fauziah Yarsi Mataram - Marzuki Marzuki*; Ahmad Sulhan; Muchammadun Muchammadun (Riwayat: Educational Journal of History and Humanities, 2022)
Monitoring and coaching pattern head school for enhancement teacher performance at SDIT Fauziah Yarsi Mataram related supervision and coaching head school for enhancement teacher performance , obstacles faced head school for enhancement teacher performance . Study this is study approach qualitativetype approach phenomenology with method interview . Research results this showing that pattern supervision and coaching head school for enhancement teacher performance at SDIT Fauziah Yarsi Mataram about ability enhancement teacher performance with method supervision and guidance carried out by the head school knowing constraint head school for enhancement teacher performance in a professional manner, the need for enhancement teacher performance.